Privatize modification of broadband dual IP stack on cloud platform - Chengli ZHANG; Xiaorong HE; Weifang SONG (Dianxin kexue)
As IPv4 address became exhausted even sooner, China Telecom had been speeding up the IPv4/IPv6 dual IP stack construction before the final large scale application of IPv6.Meanwhile, emphasis of IPv4 address privatize modification was placed on following schedule at this very moment to ensure the smooth transition and public IPv4 address providing.By studying the trace-back model of IPv6 and private IPv4 dual stack IP address in typical telecom business scenarios, the way to separate IP address trace-back model from traditional broadband AAA platform and migrated into cloud deployment were acquired , thus provided a reference for the AAA entirety reconstruction.